The strategy of the major powers in the Greater Mekong Subregion and the possibilities of Russia’s competition with them: a view from Vietnam - Vu Thuy Trang (Восточная Азия: факты и аналитика)
The major powers are becoming more interested in the Greater Mekong Subregion (GMS) due to its strategic location. They believe that increasing their presence in the area helps to achieve a number of national goals, particularly enhancing their influence in the Asia-Pacific region as a whole as well as in the countries of mainland Southeast Asia. The article examines the US and China’s approaches to the Greater Mekong Subregion (GMS) in light of their rivalry. This analysis additionally demonstrates that every power has a unique way for creating integration mechanisms in order to draw the GMS nations under its influence. The paper also focuses on the evaluation of Russia's capabilities. The author points out that given China's and the United States' long-standing presence in the area, Russia, which has a number of interests there, must take the proper measures to establish its place and role in the region.